TV shapes presidential politics in the Kennedy-Nixon debates : an augmented reading experience - Burgan, Michael (Captured television history., 2019)
Briefly examines the history of the first-ever televised presidential political debates between John F. Kennedy and Richard Nixon and discusses how each candidate came across on TV. Argues that ever since debates became televised a candidate's image has been more important than message. Includes a timeline and glossary.